Effectiveness of Non-Invasive Methods in Studying Jaguar (Panthera onca) Hair - Rodrigues, Larissa Pereira [UNESP]; Raad, Paul [UNESP]; Santos, Daniela Carvalho dos; Almeida, Alaor Aparecido [UNESP]; Costa, Vladimir Eliodoro [UNESP]; Mota, Ligia Souza Lima Silveira da (MDPI, 2025)
Mammalian hair is a source of biological information and can be used in genetic, toxicological, hormonal, and ecological studies. However, non-invasive collection methods are still little explored. This study aimed to describe and validate a passive methodology for collecting hair from jaguars (Panthera onca) and evaluate its viability for different analyses. This study was conducted in the Northern Pantanal, where synthetic fiber mats were installed in strategic locations to passively capture hair. The presence of animals and the collection of samples were monitored by camera traps over a period of 30 days. The collected samples were subjected to morphological analyses by electron microscopy, molecular tests for genetic and sex identification, and isotopic and heavy metal analyses. The results showed that the collected hairs were well preserved, allowing the structural and molecular identification of the material. The analyses confirmed the viability of DNA for genetic studies and revealed specific concentrations of heavy metals and stable isotopes. The proposed methodology proved to be effective and is a promising alternative for obtaining samples without directly interfering with the behavior of the animals.